Dietary protein to starch metabolizable energy ratios alter growth performance and gastrointestinal microbiota of calves - Chen, Xue; Han, Zhiyi; Dong, Jianan; Xiao, Jun; Zhao, Wei; Rong, Jiye; Aschalew, Natnael D.; Zhang, Xuefeng; Qin, Guixin; Zhen, Yuguo; Sun, Zhe; Wang, Tao (Frontiers in Microbiology, 2023)
The diet structure are very important for the growth and development of calves. This study aimed to investigate the effects of dietary protein to starch metabolizable energy ratios (DPSRs) on growth performance, blood index and gastrointestinal microbiota of calves. Forty-eight Holstein bull calves were fed six dietary DPSRs including A20-35 (20% CP and 35% starch), B20-30, C20-25, D22-35, E22-30, F22-25 at d 4 to d 60, and then changed to another six dietary DPSRs at d 61 to d 180 (A18-30, B18-27, C18-24, D20-30, E20-27, F20-24). Twelve calves (d 60) from groups A20-35, C20-25, D22-35, F22-25 (n = 3) and another twelve calves (d 180) from groups A18-30, C18-24, D20-30, F20-24 (n = 3) were euthanized. The growth performance parameters were measured. Blood, ruminal fluid and cecum digesta were collected for further analysis. Results showed heart girth gain of B18-27 was significantly higher than A18-30, C18-24, and heart girth gain (d 180) was significantly affected by protein × starch (DPSRs; P<0.05). Blood urea nitrogen (BUN) (d 60) in C20-25 was significantly higher than A20-35 and B20-30 (P<0.05). The BUN (d 180) in D20-30 was significantly higher than A18-30 (P<0.05). The BUN was significantly affected by protein × starch (P<0.05) on d 60. The albumin (ALB) level in C20-25 and C18-24 were significantly higher than that in A20-35 on d 60 and A18-30 on d 180, respectively (P<0.05). The ALB level in D22-35 on d 60 and E20-27 on d 180 was significantly higher than that in other groups (P<0.05). The ALB level was significantly affected by protein and starch respectively on d 60 (P<0.05). In the rumen, the genera Roseburia (C20-25) and Dialister (D22-35), Prevotellaceae UCG-001 (C18-24), Erysipelotrichaceae UCG-002 and Anaerovorax (F20-24) were found in significant higher relative abundances than those in other groups (P<0.05). In the cecum, the genera Bacteroides and Eisenbergiella (F22-25), Ruminiclostridium_1 and Candidatus Stoquefichus (A18-30), Erysipelotrichaceae UCG-004 and Tyzzerella 4 (D20-30), Prevotellaceae UCG-003 and Klebsiella (F20-24) were found in significant higher abundances than those in other groups (P<0.05). Collectively, these results indicated that the heart girth, BUN, ALB, and gastrointestinal microbiota responded distinctly to differing DPSRs.